Battle of Forms, United Nations Convention on Contracts for the International Sale of Goods (CISG), Conflicting Contract Terms, International Sale, International Trade Law, Vienna Sale Convention - Hamid Reza Nikbakht; Shaha Jafaro NADOUSHAN (Faṣlnāmah-i Pizhūhish-i Huqūq-i Khuṣūṣī, 2015)
In the realm of commercial trade, it is a common practice that sellers and buyersmanifest their intentions to conclude the contract of sale through differentcommunications and correspondence. The parties may exchange forms andgeneral terms prepared invariably in advance for all contracts. There may be aconflict between the buyer’s and the seller’s forms. Thus, when a dispute arisesbetween the parties, the main question is whether a contract has beenconcluded, even though there are conflicting terms. If the answer is positive, afurther question is: What are the terms of this contract?By considering circumstances and conduct of the parties, on the whole, after theexchange of the forms, it can be said that there is a valid contract. A viablesolution is to disregard the conflicting terms, and instead, to consider provisionsof the law governing the contract. When CISG is the law applicable to the salecontract, its provisions may well be used to fill the gaps after conflicting termsare ruled out.